Experimental analysis and design optimization of an empty diffuser for performance Enhancement in DAWT - Mustafa A. Almaliki; Ihab Omar; Mohanned Mohammad Naji; Tabarak Jassim Alwan (Case Studies in Thermal Engineering)
With the increasing demand for clean energy, and because of the acute problems caused by fossil fuels on the environment. It has become very necessary to search for alternative energy that is inexhaustible and safe at the same time. Researchers believe that diffuser-assisted wind turbines can play an important role in solving energy problems, especially in residential areas. As it is known that energy is proportional to the cube of velocity, that is, as the air velocity increases slightly, the energy increases exponentially. This paper has focused on the flanged diffuser because it can increase the pressure drop at the outlet of the diffuser, which increases the flow velocity. The study also focused on 5 variables in the diffuser to obtain the ideal design for the diffuser, namely the length of the diffuser, the angle of inclination of the diffuser, the angle of inclination, the angle of the lip and the height of the lip. Using the CFX 3D turbulent model (SSTK-ω) ANSYS 20. The results showed that the diffuser with a 50 bevel in addition to an entry flange at an angle of 30, L/D = 0.6 and H/D = 0.3 gives a speed increase of 5 times compared to the flange normal.